Stebuklinių pasakų personažai vaikų knygų iliustracijose: slibinas ir ragana - Korsakaitė, Ingrida (Knygotyra, 1999)
Illustrated folk tales and fairy tales by Lithuanian authors make a great and valuable part of children’s books. Fantastic motifs and supernatural characters have inspired quite a few Lithuanian artists to depict them in graphics. The present article is concerned with fantastic characters, specifically antagonists such as dragons and witches, represented in Lithuanian children’s book illustrations. In stories, the character traits of these antagonists are usually described in a very laconic way; however, in illustrations, a rich and distinctive tradition of their representation has developed. The article outlines the genesis, development, localization, and controversial meaning of archaic images of dragons and witches. The author has attempted to determine the relationship of the dragon found in book illustrations with the iconography of this motif in Lithuanian folk art. Although the image of the dragon created in Lithuanian children’s books is rather varied, it is not original enough to transcend its traditional representation. Various pictorial representations of the dragon in works by A. Vaičaitis, J. Steponavičius, R. Viesulas, A. Makūnaitė, V. Valius, A. Surgailienė, B. Leonavičius, I. Žviliuvienė, K. Kasparavičius, and others have been discussed. Most often, the illustrations depict the dramatic moment of the protagonist’s fight against the dragon. The motif of the dragon chasing the nine-brothers’ sister is also rather common (this hero is very popular in Lithuanian folk tales). Book jackets and covers also frequently feature a decorative picture of the dragon, which is one of the most distinguished elements of fairy tale fantasy. In Lithuanian children’s books, a rather unique picture of the witch (a fairy or a stepmother) has formed. At the same time, a peculiar tradition of its representation has developed, which is quite different from that found in children’s book illustrations of other nations. Most often, Lithuanian artists choose to depict a witch who is a wrongdoer. Very seldom does one come across a positive, helpful witch. The most common physical appearance of the Lithuanian witch is a big crooked (long pointed) nose, loose hair hanging about and soaring in the air. As a rule, she is bareheaded. The clothes of the witch include some ethnographical elements. Moreover, the witch is most often represented in dynamic dramatic situations. The magical motif of running and chasing is also common. In illustrations, one of the most fabulous features of the witch is her ability to rush and fly. In these cases, a broom is the most common attribute. The expressive representations of the witch created by V. Jurkūnas, D. Tarabildienė, B. Žilytė, J. Steponavičius, A. Surgailienė, B. Leonavičius, A. Žvilius, S. Eidrigevičius, V. Gedmantaitė, K. Kasparavičius, and others have been discussed in the article.